Low temperature reduces occludin expression in bronchial epithelial cells: Implications in cold-induced asthma. (May 2023) - Zhou, Tingyang; Liao, Wenjing; Wang, Xiaofen; Wang, Yiyan; Yang, Pingchang; Zuo, Li; Zhang, Xiaowen
Abstract: Background: Cold exposure is a common factor to trigger asthma attacks. However, the underlying mechanism has not been thoroughly elucidated. We aimed to investigate the hypothesis that low temperature reduces occludin expression and compromises epithelial barrier function in airways, which in turn, results in asthma exacerbation. Methods: We examined occludin expression in human bronchial epithelial cell line (Beas-2B) cells exposed to either 29 °C or 37 °C. The following drugs were administered prior to cold treatment: MG132 (a proteasome inhibitor), cycloheximide (a protein synthesis inhibitor), HC-067047 plus GSK2193874 (transient receptor potential vanilloid 4 [TRPV4] antagonists), or C4-ceramide (a glucocorticoid-inducible kinase [SGK1] activator). siNedd4–2 was transfected into Beas-2B cells to investigate the role that Nedd4–2 plays in mediating occludin instability induced by cold. In animal experiments, we treated ovalbumin (OVA)-induced asthmatic mice with a thermoneutral temperature of 30 °C or cold exposure (10 °C, 6 h/day) for 2 weeks. GSK2193874 or C4-ceramide was administered during the cold treatment. Occludin expression of the lung, pulmonary permeability, serum IgE levels, and lung inflammation were assessed. Results: Low temperature treatment (29 °C) significantly reduced the expression of occludin in Beas-2B cells from 1 to 9 h, which was rescued upon treatment with MG132, HC-067047 plus GSK2193874, C4-ceramide, or Nedd4–2 knockdown. Low temperatures affected occludin stability through SGK1/Nedd4–2-dependent proteolysis. In vivo mice data revealed that cold exposure compromised the airway epithelial barrier function, decreased occludin expression, and exacerbated lung inflammation, which was attenuated by the GSK2193874 or C4-ceramide injection. Conclusion: We identified a potential mechanism underlying cold-induced asthma exacerbation involving Nedd4–2-mediated occludin proteolysis and airway epithelial barrier disruption. Highlights: Low temperature reduced occludin expression in bronchial epithelial cells. Cold-induced occludin degradation was mediated by Nedd4-2-dependent proteolysis. Reduced expression of tight junction proteins may lead to epithelial barrier dysfunction at low temperatures. C4-ceramide improved occludin expression at low temperature.